Towards a Hermeneutics of Pathetic Dots : Finding the Gap Between Law and Reality - Bart Jansen (Yuridika, 2019)
Jansen outlines the methodology of the brainstorm session concerning the findings of the various studies presented at the SMART conference in November 2017. The central questions at the conference focused on how the behaviour of producers of cotton, fabric, and ready-made garments, can be changed in favour of environmental and social sustainability. Jansen provides an interpretation of the Pathetic Dot Theory, designed by Lessig, who assigns an important role to law. In this contribution Jansen presents an approach that can be used to find out in which ways legal means can be applied to achieve an ideal relationship between men and nature